The Importance of Heart Rehabilitation for Coronary Heart Disease Patients - Husein, Muhammad (LPPM STIKES MUHAMMADIYAH GOMBONG, 2019)
Coronary heart disease has now become a global cardiovascular problem with a high mortality rate. Regarding the mortality and morbidity rates of patients with high myocardial infarction, appropriate treatment is needed for patients. Three interventions were performed on coronary heart disease patients, thrombolytic interventions, percutaneous coronary intervention, and coronary artery graft bypass (CABG). Cardiac Rehabilitation is a treatment protocol recommended for the treatment of heart disease, and has been developed from a simple multidisciplinary sponsored patient monitoring process that requires patient education, specially designed exercise programs, modification of patient risk factors, and patient benefits. Identifying incentive programs will increase the level of participation in rehabilitation programs, to help patients achieve the main benefits of cardiac rehabilitation